MYOPIA – EPIDEMIOLOGY AND MANAGEMENT IN THE PEDIATRIC POPULATION - Sebastian Kupisiak; Aneta Rostkowska; Malwina Draim; Natalia Pasierb; Michalina Kosowska; Wiktoria Dzierzgowska; Aleksandra Sowa; Kacper Trząsalski (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Myopia is currently the most prevalent refractive error worldwide, with a rapidly increasing incidence, particularly among children and adolescents in urbanized regions. This review outlines the most effective evidence-based strategies for preventing and slowing the progression of myopia, with a focus on both pharmacological and non-pharmacological approaches.The State of Knowledge: Recent studies have highlighted that increased time spent outdoors significantly reduces the onset of myopia in non-myopic children, though its effect on progression in already myopic individuals appears limited. Light exposure, especially to moderate-intensity natural light, has shown potential in mitigating axial elongation and promoting choroidal thickening. Sleep quality and duration may also influence myopia development, though further research is needed to confirm this relationship. Pharmacological intervention with low-dose atropine (particularly 0.01–0.05%) is currently the most effective and widely accepted treatment, offering substantial benefits with minimal side effects. Optical interventions such as orthokeratology, multifocal spectacle lenses, and dual-focus contact lenses have demonstrated efficacy in controlling axial elongation by modifying peripheral retinal defocus.Summary: Combining lifestyle modifications (outdoor activity and light exposure) with pharmacological (low-dose atropine) and optical (e.g., orthokeratology and bifocal lenses) interventions provides a comprehensive, multimodal strategy to manage and slow myopia progression. Early implementation of such interventions is essential in addressing the growing public health burden of myopia.